Optimisation of integrated control of ticks and tsetse flies in mixed game and livestock interfaces in Queen Elizabeth National Park, Uganda - Michael Ocaido; Celsus Sente; Judith Irene Nagasha; Daniel Kiiza; William Edyang; Fred Kanyike; Solome Namirimu (BMC Veterinary Research)
Abstract Background Mixed Game and Livestock Interfaces (MGLIs) in and around conservation areas like Queen Elizabeth National Park (QENP) have typanosomosis, tsetse flies, Ticks and Tick-Borne Diseases (TTBDs) as major constraints to livestock productivity. There were no cheaper community-based methods for controlling both ticks and tsetse flies. It was against this background that this study was done. Methods A weekly restricted spraying of cattle using vectocid ® for 6 months was done in MGLIs in QENP for controlling both ticks and tsetse flies. Before technology introduction, a baseline survey was done to establish livestock productivity, tsetse infestation and cattle tick burdens, prevalence of tick-borne diseases (TBDs) and trypanososmosis, morbidity and mortality rates due to TBDs and trypanososmosis; and the economic cost due to TTBDs, tstetse flies and trypanosomosis. Later the above parameters were monitored to quantify the impact. Results After intervention, infestations by Rhipicephalus appendiculatus (14.8 ± 0.8 / cattle), Ambylloma variegatum (0.8 / cattle) and Rhipicephalus evertsi (0.2/ cattle) decreased by 43.2%, 50% and 100% respectively. However, Rhipicephalus microplus and Rhipicephalus decoloratus infestations grew by 1000% and 400% respectively. Tsetse fly catches per trap after 72 h decreased from 14.2 to 0. The trypanosomosis prevalence in cattle decreased from 7.3% to none. The farmer reported prevalence of tryapanosomosis reduced from 31.6% to 1.1%; East Coast Fever (ECF) reduced from 12.3% to 4.3%; heartwater and anaplasmosis reduced from 4.5% and 0.7% respectively, to 0. The mortality rate of cattle due to tryapnosomosis was reduced from 7.2% to 0; ECF reduced from 3.2% to 0.6%; anaplasmosis and heartwater reduced from 0.1% and 1.1% respectively to 0. Annual mortality loss per cattle herd due to trypanosomosis and TBDs reduced by 88.3% from USD 1,571.3 to USD 184.1 after intervention. Before intervention tryapnosomosis, ECF, anaplasmosis and heartwater constituted 70.6%, 17.7%, 11.1% and 0.6% of this loss respectively. However, after intervention there was mortality loss of only USD 35.9 which occurred due to ECF. The annual economic cost of ticks, tsetse flies, TBDs and trypnosomosis decreased from USD 1,916.8 to USD 302, with return of investment of 23. Conclusions The introduced technology was effective for control of tsetse flies, R. appendiculatus, R. evertsi and A. variegatum; but not for R. decoloratus and R. microplus.